Medical treatment of vitiligo: A narrative review - Anuradha Bishnoi; K.B. Meghana; Davinder Parsad (Pigment International)
Vitiligo, a chronic skin condition characterized by depigmentation, poses significant therapeutic challenges. Various medical therapies have been explored to address this disorder, aiming to halt its progression and promote repigmentation. Recent advancements in medical therapies have shown promising results in managing this condition. This abstract reviews the latest therapeutic approaches, including the use of Janus kinase inhibitors such as ruxolitinib. Additionally, traditional treatments such as corticosteroids, calcineurin inhibitors, and phototherapy continue to play a crucial role in vitiligo management. This review highlights the importance of a multifaceted approach, combining new and established therapies to optimize patient outcomes and improve quality of life.